The Correlation between Serum TG/HDL-c Ratio and Arterial Stiffness Using The Cardio-ankle Vascular Index in Overweight or Obese Patients - Raden Mohammad Yogiarto; Andrianus Oktovianto; Ni Putu Anggun Laksmi; Johanes Nugroho Eko Putranto (Cardiovascular and Cardiometabolic Journal, 2020)
Background. The effect of increasing TG/HDL-c serum ratio, as a result of insulin resistance, is considered to have an important role in the occurrence of arterial stiffness. Increased arterial stiffness is an important marker in the development of cardiovascular disease and is a predictor of heart attack and stroke. Aims. This research was conducted to determine the relationship between the arterial stiffness assessed through non-invasive cardio-ankle vascular index (CAVI) examination and the TG/HDL-c ratio in overweight and obese individuals. Cardio-Ankle Vascular Index (CAVI) is a non-invasive clinical measurement to evaluate arterial stiffness manner and independent of blood pressure. Methods. This study is considered as correlational study using purposive sampling as the technique. Thirty-two subjects participated in this research and each of them was subjected a CAVI examination to assess arterial stiffness. Their blood samples were collected for lipid profile measurement. The data were analyzed using Pearson Correlation Test. Results. The correlation between TG/HDL-c serum level and arterial stiffness using CardioAnkle Vascular Index (CAVI) in overweight or obese patients (p <0,01) proved to be positive and significant.